Soccer academy practitioners` perceptions and application of bio-banding - Towlson, C.; Watson, D. J.; Cumming, S.; Salter, J.; Toner, J. (PLOS ONE, 2023)
The primary aims of this study were to examine the application of maturity status bio-banding within professional soccer academy programmes and understand the methods employed, the intended objectives, and the potential barriers to bio-banding. Using a mixed method design, twenty-five professional soccer academy practitioners completed an online survey designed to examine their perceptions of the influence of maturation on practice, their perceptions and application of bio-banding, and the perceived barriers to the implementation of this method. Frequency and percentages of responses for individual items were calculated. In the next phase of the study, seven participants who had experience with, or knowledge of, the bio-banding process within an academy youth soccer setting were recruited to complete a semi-structured interview. Interview data was transcribed and analysed using a combination of deductive and inductive approaches to identify key themes. The main findings across the two phases of the study were that [1] there is consensus among the practitioners that the individual effect of maturation impacts their ability to accurately assess the soccer competencies, [2] the majority (80%) of the sample had implemented bio-banding, with practitioners showing a clear preference for using the Khamis and Roche method to bio-band players, with the greatest perceived benefit being during maturity-matched formats, specifically for late or post-PHV players, [3] Practitioners perceived that bio-banding enhances their ability to assess academy soccer players, and [4] practitioners who have used bio-banding believe that the method is an effective way of enhancing the perception of challenge thereby providing a number of psycho-social benefits. Findings suggest that a collaborative and multi-disciplinary approach is required to enhance the likelihood of bio-banding being successfully implemented within the typical training schedules across the adolescent phase of the player development pathway.